Systematic Approach to Modernization of Furnace Equipment in Blank and Mechanical Assembly Production Processes at Mechanical Engineering and Automotive and Tractor Enterprises of Republic of Belarus - A. P. Nesenchuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers measures pertaining to construction of new industrial furnaces and modernization of existing ones at the plants of the Republic of Belarus. Concrete recommendations ensuring an increase of technological factor of thermal and heating furnaces up to 35–37 % that is by 2–3-fold higher in comparison with a current value of the index that shows efficiency of organic fuel usage.